Stoichiometry, surface and structural characterization of lead iodide thin films - Condeles,J. F. (2006)
In this work we present the structural properties and stoichiometry analysis of thin films of lead iodide (PbI2). This material is a very promising semiconductor material for the development of X-ray detectors in digital medical imaging. An alternative deposition method called Spray Pyrolysis was used. We discuss the main advantages and limitations of the deposition process comparing three different starting material powders. Extra iodine atmosphere during deposition and the effect of post-deposition thermal treatment is also discussed. The structural properties were studied by X-ray diffraction, Atomic Force Microscopy (AFM), Scanning Electronic Microscopy (SEM) and stoichiometry analysis were performed using Energy Dispersive Spectroscopy (EDS).